Clinicomorphological patterns in an outbreak of paederus dermatitis in patients attending rural tertiary care hospital - Bandi Niharika Reddy; Reddy, Duttala Indira; Kumar, B. Udaya; Reddy, N. Harish Kumar (International Journal of Research in Dermatology, 2024)
Background: Paederus dermatitis (PD) is an acute irritant contact dermatitis caused by beetles belonging to the genus ‘Paederus’. The study aims to describe the clinical and morphological patterns and epidemiology of PD. Methods: A descriptive study was done on 80 patients with PD attending DVL OPD in a tertiary care hospital for 6 months i.e.; from March to August 2023. A detailed clinical history was taken and local and systemic examinations were done. Results: The mean age of the patients was 24.8 years. The percentage of females affected was 61.25% and males was 38.75%. Peak cases were noted during May (32.5%) followed by August (17.5%). Out of 80 patients, 61 had erythematous plaques (76.25%) along with other types of lesions (mixed lesions), 8 had post-inflammatory hyperpigmentation (10%), 5 had bullae (6.25%), 6 had erosions alone (7.5%). Out of 61 patients with erythematous plaques, 16 had vesicles and 15 had pustules. Common sites involved were face and neck (42.5%), trunk (35%), and upper extremity (30%), 51.2% of patients were sleeping with windows open, 73.7 % of patients complained of itching, 80% of patients were residing in areas with nearby vegetations. 60% of the patients affected were students residing at college hostels in rural areas with surrounding vegetation. Conclusions: PD can present in various forms and should be promptly differentiated from other conditions. Proper education of the general population and awareness about the paederus beetles should be given.